Sustainable Personal Branding: Aligning Individual Identity with Organizational Goals in Human Resource Management - Szántó, Péter; Papp-Váry, Árpád (Journal of Cultural Analysis and Social Change, 2025)
This paper explores the intersection of Personal Branding and Sustainable Human Resource Management (HRM), addressing the research gap regarding how individual branding efforts can support sustainability within organizations. As companies increasingly align their strategies with the United Nations’ Sustainable Development Goals (SDGs), the role of employees as active contributors to these goals becomes more prominent. Personal Branding, understood as the strategic self-presentation of professionals, appears as a potential enabler of sustainable organizational culture, green HRM practices, and responsible leadership. Using a mixed-methods approach, the study combines a systematic literature review with qualitative interviews involving 12 professionals from various industries who actively integrate sustainability into their personal branding. The findings reveal that when personal branding aligns with organizational values and sustainability goals, it enhances both individual credibility and organizational commitment to Corporate Social Responsibility (CSR). Digital platforms, especially social media, were identified as powerful tools for promoting sustainability-related identity and behavior, although challenges such as organizational resistance and limited resources still exist. The study outlines key characteristics of sustainable personal branding, including authenticity, ethical communication, and alignment with long-term environmental and social objectives. It also emphasizes the importance of digital literacy and lifelong learning in building personal brands that reflect sustainability values. By supporting employees in developing sustainability-oriented personal brands, organizations can strengthen their employer brand, boost employee engagement, and contribute more effectively to global sustainability goals. This research contributes to the evolving discourse on sustainable HRM by positioning Personal Branding as both an individual strategy and an organizational asset for promoting sustainability and long-term competitiveness.